A Promising PMMA/m-MgO All-Solid-State Electrolyte for Lithium-Oxygen Batteries. Issue 2 (3rd February 2021) - Wang, Songzhao; Hu, Jiwen; Gui, Xuefeng; Lin, Shudong; Tu, Yuanyuan
Abstract : Lithium-oxygen batteries are in desperate need of stable solid-state electrolyte to replace liquid electrolyte containing potential safety hazard which can resisting the corrosion of O 2−, inhibit the formation of lithium dendrite, and prevent the chemical reaction between the lithium and the oxygen diffusing from the air positive electrode to the negative electrode. However, unfortunately, the poor ionic conductivity of the solid-state electrolyte inhibits its further application. Here, we report a stable all-solid-state composite electrolyte consisting of organic PMMA and inorganic modified MgO (m-MgO) for lithium-oxygen batteries. Owing to the introduction of stable oxygen-containing functional groups, the optimization relying on the shortened path of original ion conduction has thus improved the conduction rate. The tests on the all-solid-state electrolyte demonstrate that it possesses good ionic conductivity and a wide electrochemical window. The tests of Lithium-oxygen battery based on PMMA/m-MgO electrolyte revealed that the cycle performance is significantly improved, the polarization phenomenon is effectively controlled, and the rate performance is also enhanced.